2017
DOI: 10.1002/mas.21549
|View full text |Cite
|
Sign up to set email alerts
|

Ion traps in modern mass spectrometry

Abstract: This review is devoted to trapping mass spectrometry wherein ions are confined by electromagnetic fields for prolonged periods of time within limited volume, with mass measurement taking place within the same volume. Three major types of trapping mass spectrometers are discussed, specifically radiofrequency ion trap, Fourier transform ion cyclotron resonance and Orbitrap. While these three branches are intricately interwoven with each other over their recent history, they also differ greatly in their fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 182 publications
(280 reference statements)
1
37
0
Order By: Relevance
“…Using Eqs. (3)(4), we can then calculate the ratio of the fluorescence rates for the DBR laser and the BBL, which for P = 0.88 mW becomes 2.5, in reasonable agreement with the experimental value of 3.3 considering the simple models used and the experimental uncertainties. Equating Eqs.…”
Section: Theoretical Fluorescence Ratessupporting
confidence: 76%
“…Using Eqs. (3)(4), we can then calculate the ratio of the fluorescence rates for the DBR laser and the BBL, which for P = 0.88 mW becomes 2.5, in reasonable agreement with the experimental value of 3.3 considering the simple models used and the experimental uncertainties. Equating Eqs.…”
Section: Theoretical Fluorescence Ratessupporting
confidence: 76%
“…Though LDI was used as the primary characterization tool in the 1990s, softer techniques like matrix-assisted laser desorption ionization (MALDI) and ESI became more popular for the ionization of intact ligand-protected clusters. In 1998, Schaff et al reported a 10.4 kDa Au-GSH (GSH = glutathione) cluster, Au 28 (SG) 16 48 . The composition was proposed from both MALDI MS and ESI MS.…”
Section: Advances In the Study Of Noble Metal Clustersmentioning
confidence: 99%
“…In 2012, Yu et al reported the size controlled growth of Au 25 NCs where they slowed down the reduction rate by using CO as a mild reducing agent 100 . By using MALDI MS, the authors demonstrated that a mixture of Au [10][11][12][13][14][15] NCs was produced within 5 min of reaction, followed by the formation of Au [16][17][18][19][20][21][22][23][24][25] NCs over a period of 40 min, which finally size focussed to Au 25 NCs after 24 h. However, due to fragmentation, only the core masses could be identified, and no information was obtained about the ligand shell of the intermediate 12 Cl] + , [Ag 8 Cu 6 (C≡C t Bu) 12 Cl] + , and [Ag 14 (C≡C t Bu) 12 Br] + cluster ions showing their onsets of ionization. The yield of the product ions as a function of the photon energy is shown for [Ag 14 (C≡C t Bu) 12 Cl] 2+ , [Ag 8 Cu 6 (C≡C t Bu) 12 Cl] 2+ , and [Ag 14 (C≡C t Bu) 12 Br] 2+ .…”
Section: Resolving the Solution-phase Growth And Nucleation Of Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…For proteomic and peptidomic studies, several mass spectrometer configurations are currently available with specific strengths and weaknesses. Over the last decade, new hybrid mass spectrometers with high-resolution and accurate mass (HRAM) performances were developed and commercialized, opening up new opportunities to quantify and characterize proteins and peptides in biological matrices (Nolting, Malek, & Makarov, 2017;Vidova & Spacil, 2017;Eliuk & Makarov, 2015). These new mass analyzers have been extensively used by proteomic mass spectrometry scientists, leading to the development of several innovative analytical strategies, including data-dependent acquisition (Kalli, Smith, Sweredoski, & Hess, 2013), data-independent acquisition (DIA) (Sajic, Liu, & Aebersold, 2015), SWATH-MS (Anjo, Santa, & Manadas, 2017) and more recently, SCOUT-MRM (Rougemont et al, 2017).…”
Section: Introductionmentioning
confidence: 99%